THE SELF-MEDICATED SCHOLAR: A CROSS-SECTIONAL EXAMINATION OF UNIVERSITY STUDENTS’ SELF-CARE PRACTICES - Fatima , Ahmed Al-Farsi; Hala , Mahmoud Al-Ali; Al-Mahrouqi, Salma Ibrahim (Research Journal of Health, Medicine and Nursing, 2024)
Self-medication is a widespread global health concern, particularly prevalent among university students. This practice poses significant risks, as students often engage in selfmedication without the guidance of healthcare professionals. Our study examines the prevalence and factors contributing to self-medication among university students. We conducted a cross-sectional study involving 800 university students to gain insight into this phenomenon. Our findings reveal that selfmedication is a common practice, with approximately 62.9% of students engaging in it. Similar trends were observed in various countries, such as India and Iraq, where selfmedication rates reached approximately 92%. Reasons for selfmedication among students include the perception of mild health issues not necessitating a physician's consultation, time constraints, past experiences with medications, advice from peers, cost avoidance, easy access to medications, and the desire to minimize waiting times. These findings underscore the urgent need for educational and awareness campaigns targeted at university students to promote responsible self-care and the dangers of self-medication. Healthcare institutions and policymakers should collaborate to address this pressing issue and develop strategies to ensure the health and safety of students